The Burdens of Family Caregivers of Schizophrenia in Mauritius - Nilmala Devi Aubeeluck; Amitabye Luximon-Ramma (Ital Publication, 2020)
Introduction: Schizophrenia is a severe mental illness impacting not only on the lives of patients but also on their family members. No studies were conducted on family caregivers of patients with schizophrenia in Mauritius. Objectives: The aim of the study was to identify the impact of caregiving on the emotional, physical, social health and financial situations of family caregivers in Mauritius. Method: The study was conducted with 144 family caregivers of schizophrenia patients from the Brown Sequard Mental Health Care Centre. The caregivers were surveyed through a validated questionnaire and the data were analysed using the SPSS, Version 23. Results: Majority of the carers were female (65.3%), most were above 55 years and married (73.6%) and 46.5% studied up to secondary level. 89% did not have any informal training about caregiving  and most were unaware of  the name of the illness. The caregiver's emotion, physical, social and financial health was positively correlated with age having Pearson Correlation values of 0.218, 0.205, 0.216 and 0.192 respectively and p-values 0.009, 0.014, 0.00 and 0.021 respectively. A significant number of the respondent (82%) always worried about their own safety when the patient became violent, and most of them avoidedlarge social events with their relatives. Moreover, majority of the caregivers (62.5%), mostly the females, complained of facing financial difficulties and were dissatisfied with the Social services received during the last 12 months. Conclusion: It may be concluded that an increase in care-giving role resulted in poor emotional well-being, poor physical and social health and an increase in financial worry. This study provides an insight that may help health professionals to plan and develop better health management programs to improve the quality of life and reduce burden of family caregivers of schizophrenia patients in Mauritius.